Simulation of lovastatin production in solid-state fermentation via oil palm frond - Nata, N. A.; Farhan, Mohd Said; Shalyda, Md Shaarani; Noorlisa, Harun (Universiti Malaysia Pahang, 2021)
Lovastatin is a potent drug for lowering the blood cholesterol. It is a competitive inhibitor of 3-hyroxy3-methyl glutaryl coenzyme A (HMG-CoA) reductase, which is a key enzyme in the cholesterol production pathway. Lovastatin increases the good cholesterol or high-density lipoproteins to prevent the formation of plaque inside the blood vessels. This study aims to develop a process model of lovastatin production, produced by Monascus purpureus under solid-state fermentation using oil palm frond. SuperPro Design V9.5 software was used to develop and simulate the process model. Three parameters which are initial moisture content, composition of peptone and potassium, were varied to investigate their effects on lovastatin production. The optimum condition simulated using the process model at pH 7 with 60% initial moisture content, 0.0075 kg/hr of potassium, and 0.0075 kg/hr of peptone was able to produce 0.0288 kg/kg of lovastatin. The simulated results show good agreement with experimental work, with low percentage error of 5.77%, and provide a good approximation on the production of lovastatin under various process operating conditions.